Análise da relação entre a motivação de mestrandos e a conclusão de cursos de mestrado em gestão no contexto brasileiro - Coan, Fernanda Mosseline Josende (Universidade do Vale do Rio dos Sinos, 2020)
This study evaluated the motivation of master students in Brazilian management courses for its conclusion, considering that several situations of stress and daily difficulties can negatively affect these students, resulting in failure in completing the Master's course. For the analysis, it was used a questionnaire answered by 1,098 students who started Masters Courses in Management. The students were categorized according to the conclusion of the course, that is, if they finished, if they gave up or if they were disconnected in a period of 3 years. The operational model provided 11 hypotheses that could support the thesis: facing the difficulties establishes the relationship between self-determination and the conclusion or not of the course. From exploratory and confirmatory data analysis; from structural equation modeling and supported by the Self-Determination Theory, it can be said that the data confirmed the thesis, as well as corroborated results of similar studies. In most cases, there was Identified Extrinsic Motivation to attend the master's degree, and when asked about the difficulties, many did not classify them as difficulties. It was noticed that success in the course was associated with overcoming difficulties and with a low level of Intrinsic Motivation and high Intrinsic Motivation, that is, they suffered little internal pressure and had a lot of self-motivation, unlike those who did not finish, who faced difficulties feeling they are pressured and distressed, with a lot of external and intrinsic motivation and with low intrinsic motivation, which means that they felt pressured and with low internal motivation. The pressure to publish and the lack of time to devote to studies were the most reported difficulties. Therefore, it was concluded that these individuals sought, through the master's degree, to enter or improve their position in the job market, facing these situations as something that was part of the journey. An important contribution of this thesis consists of the EMEPSS scale, which assesses the motivation level of master and doctoral graduate students, however, one limitation was not having heard the respondents right after leaving the course. This present analysis may give rise to future studies using other methodologies, for example, qualitative, that analyze the difficulties identified in the existing relationships in this context, such as university and student, career and university, teacher and student, among others.
Keywords: Mestrado em gestão; Enfrentamento de barreiras; Fatores motivacionais; Conclusão do mestrado; Master in management; Facing barriers; Motivational factors; Master's degree; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis